A Comparative Analysis of the Mechanical Properties of Cortical–Trabecular Bone Materials and Calcium Silicate Materials for Bone Tissue Engineering Applications - Sovi Anggraini Armita Dewi; Arum Sinda Santika; Primasari Cahya Wardhani; Fajar Timur (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2026)
Biomechanical modeling of bone plays an important role in bone tissue engineering by enabling the understanding of the mechanical response of natural bone and substitute materials under physiological loading. This study aims to compare the mechanical properties of cortical–trabecular bone materials as an environment for tissue support with calcium silicate (CaSiO₃) as an engineered artificial substitute using the finite element method. A long-bone phantom model in the form of a hollow cylindrical structure was developed by separating cortical and trabecular regions and analyzed using ANSYS Workbench. The applied loading scenarios included lateral bending with a load of 500 N and axial compression with a load of 1000 N. The analyzed mechanical parameters were total deformation and equivalent (von Mises) stress. Simulation results show that cortical–trabecular bone is able to distribute stress more adaptively, with greater deformation occurring in the trabecular region and stress concentration in the cortical layer. Meanwhile, calcium silicate exhibits higher stiffness with smaller deformation but comparable maximum stress values. These findings indicate that the compatibility of mechanical properties between scaffold materials and natural bone significantly affects the effectiveness of bone tissue engineering applications.